2015
DOI: 10.1007/s10549-015-3378-3
|View full text |Cite
|
Sign up to set email alerts
|

CYP19A1 polymorphisms and clinical outcomes in postmenopausal women with hormone receptor-positive breast cancer in the BIG 1–98 trial

Abstract: To determine whether CYP19A1 polymorphisms are associated with abnormal activity of aromatase and with musculoskeletal and bone side effects of aromatase inhibitors. DNA was isolated from tumor specimens of 4861 postmenopausal women with hormone receptor-positive breast cancer enrolled in the BIG 1–98 trial to receive tamoxifen and/or letrozole for 5 years. Tumors were genotyped for six CYP19A1 polymorphisms using PCR-based methods. Associations with breast cancer-free interval (BCFI), distant recurrence-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
2
18
2
Order By: Relevance
“…However, genotypes, haplotypes, and diplotypes of CYP19A1 SNPs rs4646, rs10046, Aro1, and Aro2 were not significantly associated with a risk of early breast cancer events in the AI-treated patients. These results are in line with the recent study by of Leyland-Jones et al [ 11 ] that investigated CYP19A1 tumor genotype data in relation to endocrine treatment response in the BIG 1–98 trial, but in contrast to a previous study on genomic CYP19A1 genotypes regarding the risk of recurrence in AI-treated patients [ 13 ]. In the recent abstract by Umamasheran et al, an increased risk for breast cancer recurrence was observed among 191 Indian letrozole-treated T/T carriers of rs4646 [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, genotypes, haplotypes, and diplotypes of CYP19A1 SNPs rs4646, rs10046, Aro1, and Aro2 were not significantly associated with a risk of early breast cancer events in the AI-treated patients. These results are in line with the recent study by of Leyland-Jones et al [ 11 ] that investigated CYP19A1 tumor genotype data in relation to endocrine treatment response in the BIG 1–98 trial, but in contrast to a previous study on genomic CYP19A1 genotypes regarding the risk of recurrence in AI-treated patients [ 13 ]. In the recent abstract by Umamasheran et al, an increased risk for breast cancer recurrence was observed among 191 Indian letrozole-treated T/T carriers of rs4646 [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, endocrine resistance is a major obstacle to optimal treatment effect [ 4 ]. Several genetic markers for tamoxifen response have been proposed, although no consensus has yet been reached [ 5 11 ]. For AIs, data on genetic markers are sparse [ 10 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another CYP19A1 haplotype was associated with a poor OS, DFS, and metastasis-free survival (MFS) in premenopausal, ER-positive breast cancer patients [ 35 ]. In contrast, two other large studies found no evidence for an association of rs10046 and OS, DFS, and MFS in unselected breast cancer patients [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 90%
“…Future research for better personalized prediction of side effects, for example, on the basis of biomarkers, which are being investigated for drugs such as depot medroxyprogresterone 17 or tamoxifen, 18 could decrease the number of patients who require early removal for side effects. Until then, however, counseling should stress that there is no way to predict who will develop intolerable side effects, but that patients are welcome to return for implant removal if this happens to them.…”
Section: Discussionmentioning
confidence: 99%